2017
DOI: 10.5935/1984-0063.20170030
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Sleep Disorders: Integrative Care

Abstract: The integrative care model is rooted in a biopsychosocial approach. Integrative is a term which refers to increasing the harmony and coherence of your whole being, and integrative care is therefore focused on the person, not on either the disease or a therapy. It is provided collaboratively by a health team comprising physicians, psychologists, physiotherapists, acupuncturists, and meditation, nutrition, and floral therapy. Previous studies have demonstrated that interventions based on the integrative care mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Furthermore, depressive and anxiety symptoms are more evident in females than in males, and some studies have indicated an association between mood symptoms and sleep problems in females [21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, depressive and anxiety symptoms are more evident in females than in males, and some studies have indicated an association between mood symptoms and sleep problems in females [21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Working women often fall into chronic sleep disorders, even leading to other comorbid conditions without realizing it. 21 Unmarried female workers should also take into account their position as the backbone in terms of the financial and functional aspects of a family, especially when their parents are retired. 20 In women, the problem of subpar sleep quality has a pervasiveness of 47%, especially if they sleep for fewer than six hours per night.…”
Section: Respondent Background Differencementioning
confidence: 99%
“…22 Sleep disturbances and changes in sleep quality in women are related to the presence of estrogenic receptors in brain areas linked with sleep regulation. 21 These receptors translate the level of estrogen in a woman's body, which is positively correlated with better sleep quality than at higher levels of progesterone. Unfortunately, the younger the age group, the more susceptible to fluctuations in sleep quality that can interfere with estrogenic receptor function.…”
Section: Respondent Background Differencementioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that mood disorders and sleep disturbances are more prevalent in females (1.3 to 1.8 times more than men), 2 one may theorize that the prevalence of sleep disturbance in gynaecologic malignancies is greater than that of general population.…”
mentioning
confidence: 99%